Fungal conservation through a private initiative: the Mushroom Research Centre (MRC) in Thailand - Rojas Alvarado, Carlos Alonso (2004)
The conservation of fungi is an integral part of ecosystem conservation. The Mushroom Research Centre's strategic approach to fungal conservation offers valuable insights. Located in northern Thailand, this institution has emerged as a research and training hub for mycologists across Asia, providing them with practical knowledge and skills. Its influence has not been limited to the region, making it a compelling case study for the potential impact of private conservation initiatives.